Nanocrystalline HZSM‐5prepared by supercritical hydrothermal synthesis and its catalytic esterification performances. Issue 9 (2nd March 2023) - Zhang, Br. Yundi; Cui, Mingyu; Zhang, Yidong; Xu, Wei; Wang, Min; Shao, Rong; Ding, Jianfei
Abstract: The nanocrystalline HZSM‐5 was synthesized by supercritical hydrothermal synthesis for the first time and investigated in catalytic esterification of pyromellitic dianhydride(PMD)and n‐butanol to tetrabutyl pyromellitate(TBPM). The HZSM‐5 prepared by conventional hydrothermal synthesis was also examined for comparison. The catalysts were studied using XRD, N2 adsorption, NH3 ‐TPD, Pyridine‐adsorption FT‐IR, SEM, [27] Al MAS NMRandCHNS analysis. According to the results of characterization, the supercritical hydrothermal condition was helpful to reduce the size of crystal particles and improve the crystallinity of HZSM‐5, and shorten the crystallization time. The surface area, especially external surface area, and pore volume were increased, and the total acidity was increased. The strong acid sites were transformed into the weak acid sites, and the strength of weak and strong acid was weakened. The amount of framework tetrahedral Al species and Brönsted acid sites were increased. Therefore, the formation of coke was retarded, and thePMD conversion, the TBPM selectivity and the catalytic stability were obviously improved. Abstract : The PMD conversion, TBPM selectivity, yield and the catalytic stability were obviously improved on the nanocrystalline HZSM‐5 (Z‐1) prepared by supercritical hydrothermal synthesis, because it had more amount of framework tetrahedral Al species and the total acidity, higher surface area and pore volume than those of HZSM‐5 (Z‐2) prepared by conventional hydrothermal synthesis.